Chemical and structural analysis of graphene oxide reduced with naringenin: A natural product-based alternative - Antonio Augusto Martins Pereira Junior; Filipe Kayodè Felisberto dos Santos; Filipe de Almeida Araújo; Odilon Souza Leite-Barbosa; Leandra Altoé; Valdir Florêncio Veiga-Junior (Journal of Materials Research and Technology)
A strategy to produce graphene is to reduce graphene oxide (GO) to generate reduced GO (RGO) using chemical reducers, such as ascorbid acid, hydrazine and sodium borohydride, that present technical and socio-environmental issues related to the use of hazardous chemical compounds. At the present work, naringenin, a natural flavonoid present in citrus industry residues, was used as a new, safer and green reducing agent of GO to procuce RGO. Morphological analysis via SEM revealed a veil-like structure with fewer wrinkles and agglomerates in RGO/naringenin samples. XRD analysis showed the disappearance of the GO peak at 10° and the emergence of a broad shoulder around 26°, indicating partial restoration of graphitic domains. FTIR spectra indicated a significant decrease in O–H and CO bands, consistent with removal of oxygen-containing groups. Raman analysis demonstrated a reduction in structural defects, with the ID/IG ratio decreasing from 1.03 (GO) to 0.93 (RGO/naringenin). TGA results showed improved thermal stability, with an increase in residual mass from 26.6% (pure RGO) to 34.1% (RGO/naringenin). DSC analysis corroborated these findings by displaying milder exothermic events. These results confirm the efficacy of naringenin as a sustainable and efficient reducing agent for RGO production.